La plataforma Moodle: un medio de enseñanza eficaz para la comprensión lectora de textos científicos en inglés - Madruga Rios, Oraily (2024)
In the 2020 academic year , using Moodle platform was crucial to the Cuban formative process, which had to apply distance modality at the Higher Institute of Applied Technologies and Sciences, University of Havana, due to Covid-19 pandemic. Consequently, Moodle has become an effective teaching means in the subject "English (B1) with a scientific approach", focused on reading comprehension of scientific texts. The research aims at reviewing  the perceptions of students and professors on the use of Moodle for reading comprehension of scientific texts in English. The study uses synthetic-analytical, historical-logical and documentary analysis methods whilst a poll, interview and Iadov technique demonstrate Moodle leverages. As a result, Moodle turns out to be intuitive, dynamic and attractive for students. In conclusion, Moodle helped them to improve their linguistic competence substantially. Meanwhile, teachers believe that such platform makes students less shy, which leads to active participation, continuous learning, and a strengthening of digital linguistic competencies.